Design and development of an electric vertical take off and landing aircraft system control using sliding mode control system - Souza, Daniel Florêncio de (2024)
Advanced Air Mobility (AAM) is a revolutionary Air Urban Vehicle (AUV) transportation system emerging through the deployment of electric Vertical Takeoff and Landing (eVTOL). New propulsion systems, sensor technology, artificial intelligence and operational system autonomy are transforming the short to mid-range aviation industry. The principal challenge of the study presented here is to evaluate the control strategy of nonlinear dynamic systems in eVTOLs, with a particular focus on optimization within an operational domain. In order to optimize the technical capabilities of the aircraft, as well as air traffic management and safety systems for potential risks and threats during eVTOL operation, the control technique chosen for the research was the Sliding Mode Control (SMC). The control input is designed to utilize SMC principles to optimize the performance characteristics and the system's behavior for the eVTOL. The design of the control law is based on the performance of the control inputs in relation to the system's current state. Consequently, control strategies designed to attain optimal longitudinal and lateral stability to ensure the safety, stability and efficiency of flight for eVTOL, a nonlinear control system was designed which employs Sliding Mode Control (SMC). This approach is tolerant of disturbances and noise, which are typical of the eVTOL system in dynamic and uncertain urban environments during flight phases. This study presents a succinct comparative analysis of SMC and PIC control techniques, with stability as the criterion for evaluation.